Teologi Paulus tentang Kerajaan Allah dan Nilai Partisipasi dalam Budaya Batak - Selviana Putri Naibaho; Remita Nian Permata Zendrato; Yersi Hotmauli Berutu; Kevin Boris Anugrah Marbun (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
Paul's theology of the Kingdom of God provides a profound understanding of God's governance that is already present and continues to develop in the lives of humanity. This concept encourages Christians to live according to Christian values such as love, justice, forgiveness, and peace. In Batak society, which upholds the principles of Dalihan Na Tolu and mutual cooperation, the values of the Kingdom of God can be integrated with local traditions to create social harmony. Active participation in the community through customary practices and social activities becomes a tangible manifestation of Paul's teachings about the Kingdom of God. Furthermore, this understanding offers hope and strength to Batak Christians in facing life's challenges, making their identity as citizens of the Kingdom of God a source of spiritual motivation. The integration of Paul's theology and Batak culture not only enriches local traditions but also strengthens Christian faith identity within the community. Through this contextual approach, a synergy between faith and culture is created, positively impacting daily life.